Aging-related fears and their associations with ideal life expectancy - Rupprecht, Fiona; Martin, Kristina; Lang, Frieder (European Journal of Ageing, 2021)
Fears regarding various aspects tend to stimulate individuals to escape or to avoid the sources of the threat. We concluded that fears associated with the future aging process, like the fear of aging-related diseases, the fear of loneliness in old age, and the fear of death, would stimulate patterns of avoidance when it comes to ideal life expectancy. We expected fear of aging-related diseases and fear of loneliness in old age to be related to lower ideal life expectancies. We expected fear of death to be related to higher ideal life expectancies. In two adult lifespan samples [N1 = 1065 and N2 = 591; ages ranging from 18 to 95 years, M (SD)1 = 58.1 (17.2) years, M (SD)2 = 52.6 (18.1) years], we were able to support our hypothesis regarding fear of death. We furthermore found significant interactions among the fears, indicating that individuals fearing diseases or loneliness but being unafraid of death opted for the shortest lives. Our results indicate that fears regarding life in very old age might be associated with the wish to avoid this age period; the fear of death was however associated with the wish for particularly long lives, and thus, with distancing oneself from the dreaded event of death. We conclude that fears seem to be associated with how individuals approach old age and with what they wish for in their own future as aged people.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Aging-related fears; Fear of death; Ideal life expectancy; Longevity desires

COVID-19 and Perceiving Finitude: Associations With Future Time Perspective, Death Anxiety, and Ideal Life Expectancy - Rupprecht, Fiona; Martin, Kristina; Kamin, Stefan; Lang, Frieder (Psychology and Aging, 2021)
The coronavirus pandemic threatens the health, future, and life of individuals and might hence accentuate perceptions of the fragility and finitude of life. We investigated how different perceptions of the pandemic (regarding the virus as a health threat and perceiving social and financial restrictions due to the pandemic) relate to different perceptions of life’s finitude (i.e., future time perspective, death anxiety, and ideal life expectancy). Using longitudinal data from 1,042 adults (68% women; aged 18–95 years) gathered within the first and within the second peak of the pandemic in Germany, we expected decreases in future time perspective and ideal life expectancy, as well as increases in death anxiety in response to threatening perceptions of the pandemic. The results indicated decreasing future time perspectives, an accentuation of death anxiety right at the beginning of the pandemic, as well as stable ideal life expectancies. There was a tendency for more pronounced change among older adults. Initial levels and changes in the perceptions of finitude could partly be explained by initial and changing perceptions of the pandemic. Next to perceptions targeting the threat of the virus itself, perceptions of strong social and financial restrictions during the pandemic contributed to an altered stance toward the finitude of life. Concluding, we discuss stability and variation in perceptions of the finitude of life during a time of major societal change and a potentially lifethreatening pandemic.
CRIS-Team Scopus Importer:2021-12-17
Keywords: coronavirus pandemic; death anxiety; finitude of life; future time perspective; ideal life expectancy

COVID-19 Worries Predict Aging Preparation: Culture- and Domain-Specific Perspectives - Kim-Knauß, Yaeji; Lang, Frieder; Rupprecht, Fiona; Martin, Kristina; Fung, Helene H. (The journals of gerontology. Series B, Psychological sciences and social sciences, 2022)
OBJECTIVES: We investigated whether worrying about coronavirus disease 2019 (COVID-19) predicts people's engagement in aging preparation. Furthermore, we expected that this association would have culture- (i.e., Hong Kong and Germany) and domain-specific (i.e., finances, housing, care needs, connectedness, and end-of-life) tendencies, as the culture and domains that are most severely hit by the pandemic differ. METHODS: A total of 360 and 1,294 adults (aged 18-98 years) living in Hong Kong and Germany, respectively, participated in a web-based study. We fitted our data to a multilevel model in order to take into account the interdependence of domains (i.e., Level 1) within the same individual (i.e., Level 2). RESULTS: The results revealed that reporting higher COVID-19 worries were associated with pandemic-induced aging preparation, and this association was particularly apparent for Germans in comparison to those from Hong Kong. When domains were specified, this cultural difference appeared significantly stronger for the domains of care, connectedness, and end-of-life than finances and housing. DISCUSSION: Findings imply that worrying about the COVID-19 pandemic predicts people to engage in aging preparation particularly in the culture and domains most affected by the pandemic. These results from those worried about the virus may be attributed to the increased self-relevance to the topic and hence motivation.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Coping behavior; End-of-life; Future care needs; Social relations

Dementia Worry and the Perception of Personal Risk: A Longitudinal Study - Martin, Kristina; Lang, Frieder; Rupprecht, Roland; Nömer, Jessica (GeroPsych, 2020)
The research examined dementia worry and the perception of personal dementia risk based on a 2-year longitudinal online study (N = 129, 21-79 yrs). Participants completed questionnaires on attitudes, experiences, and worries concerning dementia. A fully saturated cross-lagged model was estimated. Results show that dementia worry was moderately stable, and that changes were unrelated to perceived risk or family history. In contrast, perceived dementia risk was more prone to change and was positively associated with prior dementia worry but not vice versa. Having a family history of dementia was cross-sectionally, but not longitudinally, associated with greater worry and higher perceived risk. Because of the limited variability of dementia worry, focusing on perception of personal risk is a promising approach. Future research may benefit from differentiating the plasticity of the two constructs.
CRIS-Team Scopus Importer:2020-10-30
Keywords: dementia worry; family history of dementia; risk perception; stability